Optimism, Social Identity, Mental Health: Findings Form Tibetan College Students in China - Chen, Yongyong; Su, Jing; Zhang, Yi; Yan, Wenfan (Frontiers in Psychology, 2021)
This study aimed to explore the mediating effect of social identity on the relationship between optimism and mental health among 680 Tibetan college students in China. We used the Depression Anxiety and Stress Scales, the Satisfaction with Life Scale, and the Positive Affect Scale, and developed a tool to assess optimism, which included three subscales measuring optimistic tendency, pessimistic tendency, and self-efficacy optimism. In addition, we have developed a social identity scale for Tibetan college students. Results indicated that Tibetan college students’ optimism had a significant positive impact on their mental health, and that social identity can affect their optimism to further improve their mental health. These findings provide guidance for implementing psychological interventions aimed at enhancing undergraduates’ mental health.